Clinicopathological and Molecular Features of Colorectal Cancer Patients With Mucinous and Non-Mucinous Adenocarcinoma - Lan, Yuan-Tzu; Chang, Shih-Ching; Lin, Pei-Ching; Lin, Chun-Chi; Lin, Hung-Hsin; Huang, Shen-Chieh; Lin, Chien-Hsing; Liang, Wen-Yi; Chen, Wei-Shone; Jiang, Jeng-Kai; Lin, Jen-Kou; Yang, Shung-Haur (Frontiers in Oncology, 2021)
Background: The prognosis of mucinous adenocarcinoma (MAC) and nonmucinous adenocarcinoma (NMAC) in colorectal cancer (CRC) is controversial, and the molecular differences between them is unclear. Methods: Between 2000 and 2010, a total of 1483 CRC patients were included. Among them, 73 patients (4.9%) were diagnosed with MAC. The clinicopathological features and genetic alterations were compared between MAC and NMAC. Results: After propensity score matching to balance age and sex between MAC and NMAC patients, 292 CRC patients (73 MAC and 219 NMAC) were enrolled in the analysis at a 1:3 ratio. In right-sided colon cancer, patients with MAC were more likely to have Borrmann types 3 & 4 tumors, poor differentiation, and advanced T category and tumor, node, metastasis (TNM) stage, chemotherapy, and a similar 5-year overall survival (OS) rate compared with patients with NMAC. In left-sided colon cancer and rectal cancer, patients with MAC were more likely to have Borrmann types 3&4 tumors, poor differentiation, lymphovascular invasion, advanced T and N categories and TNM stages, chemotherapy, and a worse 5-year OS rate than patients with NMAC. Regarding genetic alterations, for NMAC, right-sided colon cancer had more BRAF mutations than left-sided colon cancer and rectal cancer. For MAC, right-sided colon cancer was associated with more microsatellite instability-high tumors and more AKT1 mutations than left-sided colon cancer and rectal cancer. Conclusion: The genetic alterations are distinct between MAC and NMAC in CRC. Tumor location may have an impact on genetic alterations and patient prognosis in MAC and NMAC.